Effects of agomelatine on electrocorticogram activity on penicillin-induced seizure model of rats. (18th January 2019) - Ethemoglu, M.S.; Kutlu, S.; Seker, F.B.; Erdogan, C.S.; Bingol, C.A.; Yilmaz, B.
Highlights: Pre-administration of 50 mg/kg, but not 10 and 100 mg/kg agomelatine reduced the spike frequency significantly. 50 mg/kg agomelatine did not change the amplitude significantly after penicillin induction. VGLUT1 and VGAT tended to increase and decrease, respectively, and VGLUT1/VGAT did not change upon 50 mg/kg administration. Abstract: Agomelatine is a new antidepressant drug acting as an antagonist of 5-hydroxytryptamine receptor 2C (5-HTR2C ) and agonist of melatonergic receptors 1 and 2 (MT1 and MT2 ). Because of this dual action, it is an atypical antidepressant. The aim of this study was to investigate chronic anticonvulsant effects of agomelatine on penicillin-induced epilepsy model. Adult male Sprague–Dawley rats divided into four groups and were administered with tap water (vehicle), and agomelatine doses of 10 mg/kg, 50 mg/kg and 100 mg/kg for 14 days via oral gavage. After the last doses were given, epileptic seizures were induced by intracortical penicillin (500 IU/2.5 μl) application in rats under urethane (1.25 g/kg intraperitoneal) anesthesia. Electrocorticogram (ECoG) recordings were obtained from the somatomotor cortex through 90 min, and spike frequencies and amplitudes were analyzed. The spike frequency analyses revealed that only 50 mg/kg agomelatine administration decreased the spike frequencies of hypersynchronous discharge of neurons caused by penicillin (p < 0.05). No significant differences in amplitudes between experimental groups were observed. In addition, mRNA expressions of vesicular glutamate transporter 1 (VGLUT1) and vesicular gamma-aminobutyric acid transporter (VGAT) in response to the agomelatine active dose, 50 mg/kg, showed no significant effect of agomelatine on the mRNA expression. Our results indicate that chronic treatment with agomelatine may have potential anticonvulsant effects. Agomelatine may be a promising drug for epilepsy patients having depression due to its antiepileptic and antidepressant effects.